Free vibrations of thin plates with transversally graded structure = Drgania swobodne płyt cienkich o poprzecznej gradacji własności - Kaźmierczak, Magda; Jędrysiak, Jarosław; Wirowski, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this note vibrations of thin composite plates with a smooth and a slow gradation of macroscopic properties are considered. Plates of this kind have transversally graded macrostructure. In this paper certain averaged mathematical models of these plates are proposed. In an example, these models are applied to obtain fundamental free vibrations frequencies of a plate band, using the finite differences method.
Keywords: cienkie płyty kompozytowe; płyty cienkie; poprzeczna gradacja struktury; drgania swobodne; thin plates; transversally graded structure; free vibrations